Effects of Dietary Energy and Protein on Growth Performance and Carcass Quality of Broilers during Starter Phase - Niu, Zhuye; Shi, Jingsong; Liu, Fuzhu; Wang, Xianhui; Gao, Chunqi; Yao, Likai (International Journal of Poultry Science, 2009)
A 3x4 factorial arrangement with three Metabolizable Energy (ME) levels (12.13, 12.55, 12.97 MJ/kg) and four Crude Protein (CP) levels (20.0, 21.0, 22.0 and 23.0%), respectively, was undertaken to investigate the influence of varying levels of dietary energy and protein on broiler performance and carcass quality from 1-21 d aysof age. Six hundred 1 day old broiler chicks were randomly divided into 12 treatments, each of which had five replicates of 10 birds. BW of 21 days of age was significantly increased with an increase in dietary ME (p0.05). Both ME and CP significantly improved feed efficiency (P